Indonesian Jokes on Tailgates and Posters in English - Angelina Diva; Barli Bram (Vivid: Journal of Language and Literature, 2020)
This paper investigated jokes written on tailgates and posters in English in an Indonesian context to identify and understand the different variations of the joke meanings as non-verbal communication. Data, consisting of jokes on tailgates and posters, were collected online and examined phonologically and pragmatically using a document analysis. The data were analyzed in order to identify, categorize and classify the words and phonics and then interpret the meanings. Results showed that three jokes written on tailgates and two jokes written on posters contained funny or amusing aspects due to phonological and pragmatic factors, as in “She Book Carry Do It” which means “Sibuk Cari Duit” in Indonesian and “Busy to find money” in English.